Digital absence innovation in the enforcement of employee work discipline at the Makassar City education office - A. Rahmatia; Andi Fitiah; Risqah Amaliah Kasman; Amina Ramadana N; Dewi Hartini; Rosnaeni Arsyad; Andi Mastur; Muhammad Ridwan (Privietlab, 2026)
This study aims to analyze and explain digital attendance innovation in enforcing employee work discipline, along with the supporting and inhibiting factors that influence its implementation. This research uses a qualitative method with a descriptive approach to gain an in-depth understanding of how digital attendance functions within an organizational setting. Data were collected through observations, interviews, and documentation, allowing the researcher to capture the real conditions and employee experiences. The data analysis process followed the stages of data collection, condensation, display, and conclusion drawing to ensure systematic and comprehensive interpretation. The findings show that the digital attendance innovation at the Makassar City Education Office is effective when evaluated using an innovation model approach. In terms of relative advantage, the system saves employees’ time in recording attendance and reduces the inefficiencies found in manual systems. Regarding suitability, the system aligns well with organizational needs in promoting discipline, although employee discipline is also influenced by other factors, such as work culture and supervision. From the perspective of complexity, several technical challenges were identified, particularly during power outages, which prevented the attendance machine from operating properly. In terms of trialability, employees can operate the system easily because of its practical design and simple procedures. Finally, in terms of observability, digital attendance enables supervisors and operators to monitor attendance data transparently and detect potential fraud, such as employees attempting to entrust attendance to others. Overall, digital attendance serves as an important tool for strengthening employee work discipline.